Health Care, Health Status and Labour Productivity in Nigeria - Onyema, Joseph I.; Nyenke, Christian Ugondah (NIU Journal of Social Sciences, 2019)
The debate on the role of health in productivity of labour is an age-long one. The health conditions of the workforce affect its level of productivity. This study examined health care, health status and productivity of labour in Nigeria in order to determine the direction of causality between them. Data were collected from the Central Bank of Nigeria (CBN) Statistical bulletin and World Bank Development Indicators. The ordinary least squares (OLS) method was used to estimate the model. The analysis indicates that government expenditure on health (GXH) and life expectancy (LXP) do not conform to theoretical expectations. This can be attributed to institutional corruption and poor government attention to the provision of health needs of the people that meet global best practices. On the other hand, prevalence of HIV and AIDS (HAD) and risk of catastrophic expenditure on surgical care (RCES) are consistent with theoretic expectations. The analysis also reveals that prevalence of HIV/AIDS is statistically significant. However, GXH, RCES and LXP are not statistically significant. Pairwise granger causality test indicates that government expenditure on health (GXH) and life expectancy (LXP) does not granger cause labour productivity (LPD). But prevalence of HIV/AIDS (HAD) and poor expenditure on surgical care (RCES) granger cause labour productivity (LPD) implying that poor health care delivery and status of health of the people adversely affect labour productivity in Nigeria. The study recommends that: the government should increase its expenditure on health care facilities and personnel development. This has the capacity of reducing the risk of catastrophic expenditure on surgical care, improve the health status of the active population, boost productivity level and encourage economic development in Nigeria. Keywords: Health care, health status, catastrophic health expenditure, labour productivity.